Islamophobia Dan Dampaknya Bagi Kehidupan Beragama Di Indonesia - Bintang Rosada (UIN Mataram, 2022)
Abstract The collapse of the US superpower WTC and the Pentagon In 2011 which was done by Osama Bin Laden and his Al Qaeda network, made the negative impact into Islam and Muslims, created image that far from the real essence of Islam. A series of suicide bombings in the name of Jihad, has brought the negative essence of Islam far from its nature; peace. In the end, Islamophobia emerged as a fear of Islam and of all matter that related to it. This study try to to reveal the emergence of Islamophobia in Indonesia and its impact on the harmony between religions in Indonesia. This research is a qualitative research, with the library research methods. The data were taken from journals, e-books, bulletins, dissertations, theses, and other literatures. The purpose of this study is to explain the emerge of islamophobia and its impact. The result of this study is that the emergence of Islamophobia begins with a person's fear of the repetition of the glory of Islam as in its previous golden age. The danger of Islamophobia is always accompanied by suspicious, false perception and in long term can abolish the harmony between religions in Indonesia